Development and evaluation of tenera oil palm progenies derived from single, double and three-way crosses - Sritharan, Kandha (2020)
Commercial oil palm plantings in Malaysia are primarily composed of single crosses. These crosses have limitations in their genetic potential, thus hindering efforts for further yield improvements. The primary objective of this study was to evaluate the yield potential, bunch characteristics and vegetative traits of oil palm progenies created from single (SC), three-way (TW) and double crosses (DC) and to assess their suitability for higher density planting. Thirty Dura x Pisifera (D × P) crosses were created using different parental lines to produce three samples of varying cross types, SC (10), TW (10) and DC (10) and planted in a randomized complete block design (RCBD) with three replicates (16 palms per replication). Except for a single round of vegetative measurements, palm yields and bunch characteristics were evaluated for a period of five years. All data were analysed using a Statistical Analysis Software (SAS ver. 9.4). The yield performance summarized by cross type showed significantly higher fresh fruit bunch (FFB) production in DC (210.42 kg per palm per year) compared to SC (187.00) and TW (196.94). The highest broad sense heritability estimates calculated decreases in the order: SC > TW > DC. There were no significant differences between the three cross types for all the bunch components analysed except for mean weight per fruit (MWF); approximately 17% higher in both TW and DC compared to SC. Estimated fresh fruit bunch yields per hectare (FFBHa) was 12.5 and 6.8% higher in DC compared to SC and TW, respectively. Oil yield per hectare (OHa) and oil yield per palm (OYP) for DC was 17.6 and 10.7% higher than SC and TW, respectively. There were no significant differences between cross types for any of the vegetative traits quantified in this study. For the same parameters, within crop types, DC showed the most significant differences between progenies indicating the highest segregation of vegetative traits. Progenies DC2, SC8, DC9, TW7, TW2, SC1, SC3 and DC1 with short fronds showed the greatest potential for higher density planting. The DC2 with the shortest fronds planted at a density of 201 palms per hectare is estimated to yield 10.66 t ha-1 oil annually. Strong significant positive correlations existed between OYP/OHa and average bunch weight (BWT), mesocarp to bunch ratio (MB), oil to bunch ratio (OB) and FFBHa. There was no significant correlations observed between any of the vegetative traits with yield or bunch components. Path coefficient analysis carried out showed contrasting results between SC and both TW and DC. In all three cross types however, fruit to bunch ratio (FB) and MB possessed the greatest influence over OHa both as a direct effect and indirect effect through other traits. Creation of multiway crosses did improve yield potentials with DC showing a clear advantage over the others. The creation of multiway crosses is therefore a vital step in breeding leading to higher segregation enabling the selection of an array of traits useful in the endeavours to improve commercial yields nationwide.